2021
DOI: 10.1002/er.6815
|View full text |Cite
|
Sign up to set email alerts
|

Optimum energy analysis of separation and purification units for bioethanol production by the use of lignocellulose feedstock

Abstract: Global concerns over environmental issues raised several efforts to find an applicable alternative solution. One of the vital solutions is to promote liquid bio-refinery products as a transportation fuel. Bioethanol, considered the most common in this category, has several advantages that can help to protect the environment. However, nowadays, the production of this fuel, due to its high level of energy requirement, is not cost-effective in many countries. The current research aims to conduct Energy analysis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…However, they are still the preferred approach for large-scale bioethanol fuel generation despite this main disadvantage. Hajinezhad et al reported that the distillation unit consumed about 70% of the total energy requirements for the procedure to produce 99.5 wt.% bioethanol [153].…”
Section: Separation Of Bioethanolmentioning
confidence: 99%
“…However, they are still the preferred approach for large-scale bioethanol fuel generation despite this main disadvantage. Hajinezhad et al reported that the distillation unit consumed about 70% of the total energy requirements for the procedure to produce 99.5 wt.% bioethanol [153].…”
Section: Separation Of Bioethanolmentioning
confidence: 99%